THE TRANSFORMATION OF EDUCATIONAL COMMUNICATION IN THE ERA OF SMART TECHNOLOGY: THE INTEGRATION OF ARTIFICIAL INTELLIGENCE AND DIGITAL MEDIA IN ENHANCING ACADEMIC COMMUNICATION LITERACY - Abdul Wahab Syakhrani (INJOSEDU: International Journal of Social and Education, 2026)
The era of smart technology has transformed the paradigm of educational communication through the integration of Artificial Intelligence (AI) and digital media, which has significantly enhanced academic communication literacy. This study examines this transformation through two main discussions: (1) the role of AI in personalising learning through educational chatbots, automated writing tools, and adaptive learning systems that provide real-time feedback to improve students’ writing and critical thinking skills; and (2) digital media strategies such as Learning Management Systems (LMS), online discussion forums, and collaborative platforms that facilitate global interaction and the production of multimedia content. Using a qualitative literature review approach, this study identifies the synergy between AI and digital media in creating an adaptive and inclusive learning ecosystem, despite facing ethical challenges such as plagiarism, technological dependency, and the digital access gap. The findings confirm that a holistic approach integrating AI ethics regulation, digital literacy training, and equitable infrastructure is necessary to optimise this transformation. The conclusion offers recommendations for the development of technology literacy curricula and institutional collaboration to prepare graduates for the era of digital disruption. Overall, the integration of AI and digital media is not merely a technical innovation, but the foundation of sustainable higher education in the 21st century.